Analisis Penerapan Ice Breaking untuk Meningkatkan Semangat Belajar Siswa pada Pembelajaran IPS - Nurhidayah, Nurhidayah; Muzakir, Muzakir; Suandi, Suandi (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study aims to analyze the implementation of ice breaking as a learning strategy to improve students’ enthusiasm in Social Studies (IPS) learning for grade I students at MTs Raudlatul Ulum Batu Jangkih. The research was motivated by the low learning spirit of students, characterized by lack of focus, boredom, and minimal enthusiasm in the classroom. A qualitative approach with a case study method was employed. The participants included the school principal, a Social Studies teacher, and first-grade students. Data collection instruments consisted of observation sheets, interview guidelines, and documentation. Data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that implementing ice breaking activities at the beginning and middle of the lesson successfully created a more conducive learning atmosphere, enhanced student focus, and fostered motivation. Simple activities such as picture guessing, cheers, and clapping were effective in increasing student engagement and improving teacher-student interaction. These results highlight that ice breaking is a relevant learning strategy to reduce boredom and encourage an active and enjoyable learning environment.